SOSIALISASI PEMANFAATAN LIMBAH DAUN KAYU PUTIH (Melaleuca cajuputi) SEBAGAI PUPUK ORGANIK PADA KELOMPOK USAHA PERHUTANAN SOSIAL (KUPS) DUSUN WELNEWEN DESA WASPAIT KECAMATAN FENALEISELA KABUPATEN BURU - Tetelay, Febian Filiph; Siahaya, Ludia; Putuhena, Jusmy D; Siahaya, Troice E. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2024)
Socialization about compost making is important considering that cajuput leaf waste left over from distillation has slightly different characteristics compared to compost material that comes from leaves or other types of plant parts. This outreach aims to increase public knowledge about using leaf waste left over from distilling eucalyptus oil as raw material for making compost. The benefit is that the community can utilize wood waste left over from refining eucalyptus oil and reduce existing waste. The method used in this Community Service activity is in the form of socialization, before the activity begins, a pre-test is carried out to assess the initial knowledge of the socialization participants, then the socialization process consists of delivering material to the participants and continues with a discussion round. The activity closed by conducting a post-test on participants to assess the participants' final knowledge of the socialization material presented. The result of the socialization was an increase in the knowledge of the socialization participants regarding the use of waste leaves left over from refining cajuput oil. Participants can follow up this knowledge in the practice of using eucalyptus oil distillation leftover leaf waste in the eucalyptus oil refining business in the Social Forestry Business Group.